The relationship between transformational leadership behaviours, team leader emotional intelligence and team commitment : an exploratory study - Strauss, J. J. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA (Industrial Psychology)) -- University of Stellenbosch, 2004.